Discovery of potential Toxoplasma gondii CDPK1 inhibitors with new scaffolds based on the combination of QSAR and scaffold‐hopping method with in vitro validation. (25th February 2020) - Zhang, Pengyi; Jia, Lipei; Tian, Yafei; Xi, Lili; Duan, Ruizhi; Chen, Ximing; Xiao, Jianxi; Yao, Xiaojun; Lan, Jingfeng; Li, Shuyan
Abstract: To discover drugs for toxoplasmosis with less side‐effects and less probability to get drug resistance is eagerly appealed for pregnant women, infant or immunocompromised patients. In this work, using Tg CDPK1 as drug target, we design a method to discover new inhibitors for CDPK1 as potential drug lead for toxoplasmosis with novel scaffolds based on the combination of 2D/3D‐QSAR and scaffold‐hopping methods. All the binding sites of the potential inhibitors were checked by docking method, and only the ones that docked to the most conserved sites of Tg CDPK1, which make them have less probability to get drug resistance, were remained. As a result, 10 potential inhibitors within two new scaffolds were discovered for Tg CDPK1 with experimentally verified inhibitory activities in micromole level. The discovery of these inhibitors may contribute to the drug development for toxoplasmosis. Besides, the pipeline which is composed in this work as the combination of QSAR and scaffold‐hopping is simple, easy to repeat for researchers without need of in‐depth knowledge of pharmacology to get inhibitors with novel scaffolds, which will accelerate the procedure of drug discovery and contribute to the drug repurposing study. Abstract : A method, called CQS‐Hop, as the combination of 2D/3D‐QSAR and scaffold‐hopping methods was developed in this work to discover potential Tg CDPK1 inhibitors with new scaffolds. The inhibitory activities of these newly discovered 10 Tg CDPK1 inhibitors within two new scaffolds were experimentally validated. This CQS‐Hop method can be used as a pipeline to develop kinase inhibitors with new scaffolds.